Ethical foundations for peaceful coexistence; A cultural investigation of "keselarasan" - Yumarma, Andreas (Wacana, Journal of the Humanities of Indonesia, 2011)
Multiculturality and cultural differences are undeniable reality in both Indonesia and the world. Without wisdom such conditions can cause tensions, disputes, and conflicts. For this reason, investigation on the ethical principles contained in keselarasan can provide foundations needed for peaceful coexistence which is crucial in such multicultural conditions as are prevalent in Indonesia. Basic principles such as respect, peace, and empan papan (knowing how to place oneself) are fundamental for living in a multicultural situation. The ethical foundations in keselarasan therefore contribute solutions to manage cultural difference and multiculturalism. These are the basic principles that can help avoid violent social conflict and build peaceful togetherness and dialogue.